Caenorhabditis nematodes colonize ephemeral resource patches in neotropical forests. Issue 7 (24th July 2022) - Sloat, Solomon A.; Noble, Luke M.; Paaby, Annalise B.; Bernstein, Max; Chang, Audrey; Kaur, Taniya; Yuen, John; Tintori, Sophia C.; Jackson, Jacqueline L.; Martel, Arielle; Salome Correa, Jose A.; Stevens, Lewis; et al.
Abstract: Factors shaping the distribution and abundance of species include life‐history traits, population structure, and stochastic colonization–extinction dynamics. Field studies of model species groups help reveal the roles of these factors. Species of Caenorhabditis nematodes are highly divergent at the sequence level but exhibit highly conserved morphology, and many of these species live in sympatry on microbe‐rich patches of rotten material. Here, we use field experiments and large‐scale opportunistic collections to investigate species composition, abundance, and colonization efficiency of Caenorhabditis species in two of the world's best‐studied lowland tropical field sites: Barro Colorado Island in Panamá and La Selva in Sarapiquí, Costa Rica. We observed seven species of Caenorhabditis, four of them known only from these collections. We formally describe two species and place them within the Caenorhabditis phylogeny. While these localities contain species from many parts of the phylogeny, both localities were dominated by globally distributed androdiecious species. We found that Caenorhabditis individuals were able to colonize baits accessible only through phoresy and preferentially colonized baits that were in direct contact with the ground. We estimate the number of colonization events per patch to be low. Abstract : Caenorhabditis nematodes are real animals that live in nature. Field collections and experiments in tropical forests reveal new information about their diversity, ecology, behavior, phylogenetics, population biology, and biogeography.